2009
DOI: 10.1016/j.forsciint.2009.04.024
|View full text |Cite
|
Sign up to set email alerts
|

The spectroscopic detection of drugs of abuse on textile fibres after recovery with adhesive lifters

Abstract: Fibres are one of the most common forms of evidence associated with forensic investigations. The use of adhesive lifters to recover fibres from crime scene samples has long been established as an effective method to recover such items of evidence.Once fibres have been lifted they are transferred to evidence bags for storage, safe transport and to preserve the chain of evidence. This study shows that when fibres are tape lifted particles of substances present trapped within those fibres are also lifted.Cotton, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 11 publications
(13 reference statements)
0
12
0
Order By: Relevance
“…Katainen et al [26] reported how they could quantify the amphetamine content in seized street samples by Raman spectroscopy, using an internal phosphate ion standard. The spectroscopic detection of amphetamine (and other common drugs of abuse) on textile fibres after recovering with adhesive lifters was demonstrated by West and Went [27].…”
Section: Historical Reviewmentioning
confidence: 99%
“…Katainen et al [26] reported how they could quantify the amphetamine content in seized street samples by Raman spectroscopy, using an internal phosphate ion standard. The spectroscopic detection of amphetamine (and other common drugs of abuse) on textile fibres after recovering with adhesive lifters was demonstrated by West and Went [27].…”
Section: Historical Reviewmentioning
confidence: 99%
“…[34,35] Pure and seized samples of cocaine hydrochloride, MDMA, ketamine and amphetamine can readily be detected on a range of natural, synthetic, and dyed textiles in a range of colours from white to black. [34,35] Pure and seized samples of cocaine hydrochloride, MDMA, ketamine and amphetamine can readily be detected on a range of natural, synthetic, and dyed textiles in a range of colours from white to black.…”
Section: Detection Of Drugs On Clothingmentioning
confidence: 99%
“…They also analyze these drugs of abuse on different wool, linen and cotton fibers in colors ranging from white to black after recovery with adhesive lifters and concluded that textile fibers, lifting process, adhesive lifters and evidence bags did not interfere with the identification of drug particles embedded in fibers. 26 Raman spectroscopic method was developed to analyze and classify simulated street drug mixtures. 27 Helium-neon laser and portable Raman spectrophotometer with 785 nm laser were used to analyze the drug samples.…”
Section: Basic Principles and Instrumentationmentioning
confidence: 99%